Aplikasi Seniors Assistance System berbasis Android - Tioe Julio Adrian Sutiono; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2016)
Seniors have a weak immune system and susceptible to disease. Therefore, the elderly require special attention from their families and caregivers. The number of elderly in the world is increasing by one million per month. There are concerns on the cost and quality of care to the elderly with increasing number of elderly. These problems can be solved by using technology which is an assistive technologies that help caregivers and families monitor the daily life and maintain the health of the elderly.Seniors Assistance System applications using Android as the media of assistive technology for caregivers and families. This application helps caregivers to monitor the location of the elderly and hospital search using Google Maps technology in the application. This application can also be connected directly to the smartphone seniors with Google Cloud Messaging technology that is useful for setting automatically answer the phone, sending a warning or setting a reminder on medicine, and doctor visits.There are two applications which are seniors Android-based application and caregiver Android-based application. Caregiver’s application can monitor the location of senior’s smartphone, set reminders to take medicine as well as visits to the doctor, and send a warning to senior’s application. Senior’s application have speed dialing, search the nearest hospital, and sends SOS notification. Based on the application test, nine out of ten respondents rate the app was good overall.